Detection of anti-D and anti-G in a pregnant woman: a case report - Abdul Halim, Sarah; Mohamed Yusof, Shafini; abdullah, Marne; Iberahim, Salfarina; Zulkafli, Zefarina; Mohd Noor, Noor Haslina; Ramli, Marini; Bahar, Rosnah; Hassan, Mohd Nazri; Wan Abd Rahman, Wan Suriana (Gazi University, 2021)
Antibody identification in Rh-negative pregnant women is usually done to detect RhD alloimmunisation. The G antigen is part of the Rh blood group and is ubiquitous on most D-positive red cells. The detection of anti-G however is complicated. The objective of this case report is to highlight the importance of identifying anti G correctly especially in managing antenatal patients. We herein report a case of a 30-year-old pregnant woman, who was thought to have anti-D and anti-C on initial antibody identification, was subsequently found out to have anti-G and anti-D on further testing.